2013
DOI: 10.4244/eijv8i11a196
|View full text |Cite
|
Sign up to set email alerts
|

The CABG SYNTAX Score - an angiographic tool to grade the complexity of coronary disease following coronary artery bypass graft surgery: from the SYNTAX Left Main Angiographic (SYNTAX-LE MANS) substudy

Abstract: In this pilot study the calculation of the CABG SXscore appeared feasible, reproducible and may have a long-term prognostic role in patients with complex coronary disease undergoing surgical revascularisation. Validation of this new scoring methodology is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
236
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(251 citation statements)
references
References 57 publications
4
236
0
11
Order By: Relevance
“…All patients selected had undergone coronary angiography during hospitalization. SS analysis is only valid for natural coronary arteries, so patients with previous coronary artery bypass grafts were excluded [9]. Patients with cardiogenic shock were also excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…All patients selected had undergone coronary angiography during hospitalization. SS analysis is only valid for natural coronary arteries, so patients with previous coronary artery bypass grafts were excluded [9]. Patients with cardiogenic shock were also excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…8,20 The CSS has been proposed for evaluating the native coronary atherosclerotic burden and also for assessing the whole myocardial ischemic burden after CABG, which together could predict clinical outcomes in previous CABG surgery patients. 10,11 This study showed the clinical significance of the CSS after repeat revascularization by PCI in previous CABG surgery patients. As shown in Table 1, patients with a high post-PCI CSS had older bypass grafts, higher prevalence of CKD and peripheral artery disease, previous heart failure, lower LVEF, and a higher bCSS compared with those with low scores.…”
Section: Clinical Significance Of the Css Following Pci In Previous Cmentioning
confidence: 99%
“…The CSS was calculated to identify all coronary artery lesions on both the baseline and postprocedural coronary angiograms in accordance with a previous report 10 (Methods section and Figure I in the Data Supplement). The baseline (bCSS) and post-PCI CSS were calculated on the basis of the remaining coronary lesions before and after PCI, respectively.…”
Section: Calculating the Baseline And Post-pci Cssmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Essentially, it is the SYNTAX score of the native coronary vessels with points deducted based on the vessel-segment weighting of the bypassed coronary vessel. In such a way, it allows for a feasible and plausible calculation of the SYNTAX score in patients with prior CABG, and for the incorporation of CABG patients into contemporary trials measuring coronary complexity.…”
Section: The Syntax Score: Strengths and Weaknessesmentioning
confidence: 99%